High coercivity neodymium cerium iron boron permanent magnet and its manufacturing method and application

Optimizing the distribution of RE-rich phases at grain boundaries in neodymium cerium iron boron magnets through controlled manufacturing processes addresses the nucleation of reverse domains, resulting in improved magnetic performance and coercive force.

JP2025500990APending Publication Date: 2025-01-15YANTAI ZHENGHAI MAGNETIC MATERIAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024539035
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-27
Filing Date
2022-11-28
Publication Date
2025-01-15

AI Technical Summary

Technical Problem

The challenge in producing high-performance neodymium cerium iron boron permanent magnets lies in the formation of RE-rich phases at grain boundaries, which lead to easy nucleation of reverse magnetization domains and reduced magnetic induction strength due to mixed valence characteristics of cerium and difficulty in forming NdFe phases.

Method used

The distribution of RE-rich phases at nodular grain boundaries is optimized by ensuring they occupy at least 4% of the total area and have an average ratio of less than 30% at the intersection of three or more main phase grains, achieved through specific manufacturing processes involving milling, sintering, and aging treatments, with controlled grain boundary diffusion.

Benefits of technology

This approach enhances the magnetic performance of the magnets by suppressing reverse magnetization domains and improving the uniformity and fineness of RE-rich phase distribution, leading to higher coercive force and magnetic induction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500990000001_ABST
    Figure 2025500990000001_ABST
Patent Text Reader

Abstract

The present invention discloses a high coercive force neodymium cerium iron boron permanent magnet and its manufacturing method and application. The permanent magnet has at least one of the following characteristics: the area of ​​the RE-rich phase at the grain boundaries in the magnet occupies 4% or more of the total field area; the RE-rich phase at the grain boundaries in the magnet is uniformly and finely distributed; and the average ratio of the area of ​​the RE-rich phase at the nodular grain boundaries located at the intersections of three or more main phase crystal grains to the total area of ​​all three or more surrounding adjacent main phase crystal grains is ≦30%. The magnet manufactured by the present invention has an excellent diffusion effect when used as a grain boundary diffusion magnet base material. The RE-rich phase in the magnet is continuously distributed along the grain boundaries, providing many channels for diffusion, which is helpful to improve the diffusion depth from the diffusion source to the inside of the magnet, which is helpful to improve the distribution uniformity of the diffusion source inside the magnet, and which is helpful to improve the consistency of the internal structure components of the diffusion magnet, thereby further improving the magnetic performance of the diffusion magnet.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] This application claims priority to a prior application bearing patent application number 202111619345.1 and entitled "High coercivity neodymium cerium iron boron permanent magnet and its manufacturing method and application" filed with the State Intellectual Property Office of China on December 27, 2021. The above prior application is incorporated herein by reference in its entirety.

[0002] [Technical field] The present invention belongs to the field of rare earth permanent magnets, and in particular to high coercivity neodymium cerium iron boron permanent magnets and their manufacturing methods and applications.

[0003] [Background technology] Sintered NdFeB is a third generation rare earth permanent magnet material mainly composed of rare earth PrNd, iron, boron and other elements. Due to its excellent magnetic performance and high cost performance, it is widely used in various rare earth permanent magnet motors, smart consumer electrical products, medical equipment and other fields. With the rapid development of low-carbon environmental protection economy and high technology, the demand for NdFeB-based sintered magnets is increasing, the consumption of rare earth PrNd resources increases significantly, and the price of PrNd gradually rises. Ce is the rare earth element with the most abundant stock, with chemical properties close to PrNd. The application of Ce to sintered NdFeB instead of Pr and Nd not only reduces the cost of raw materials, but also contributes to the balanced utilization of rare earth resources.

[0004] However, due to the mixed valence characteristics of Ce, Ce with a relatively small ionic radius is prone to form CeFe2 phase, and such phase exists in the form of a single crystal grain in the magnet, so that the RE-rich phase distributed along the grain boundary is deficient between the main phase crystal grains, and the reverse magnetization domain is easy to nucleate and diffuse, making it difficult for the magnet to obtain high coercivity. At the same time, the magnetic exchange coupling action caused by the direct contact between adjacent main phase crystal grains also obviously reduces the remanence induction strength of the magnet. Meanwhile, the NdFe2 phase is difficult to form in the magnet. Therefore, in order to realize the production of high-performance Ce-rich NdCeFeB magnets, it is a technical problem to be solved to suppress the CeFe2 phase from existing in the form of crystal grains and optimize the distribution of the RE-rich phase in the NdCeFeB magnets.

[0005] Summary of the Invention In order to improve the above technical problems, the present invention provides: The area of ​​the RE-rich phase in the grain boundaries of the magnet occupies 4% or more of the total field area. The RE-rich phase is uniformly and finely distributed at the grain boundaries within the magnet. The present invention provides a neodymium cerium iron boron permanent magnet having at least one of the following characteristics: an average ratio of the area of ​​an RE-rich phase at a nodular grain boundary located at an intersection of three or more main phase crystal grains to the total area of ​​all three or more surrounding adjacent main phase crystal grains is ≦30%.

[0006] According to an embodiment of the present invention, the distribution of the RE-rich phase at the nodular grain boundary at the intersection of three or more main phase grains and surrounding all three or more adjacent main phase grains is essentially as shown in FIG.

[0007] According to an embodiment of the present invention, the RE includes neodymium (Nd) and may further include at least one selected from rare earth elements such as cerium (Ce), lanthanum (La), praseodymium (Pr), yttrium (Y), gadolinium (Gd), terbium (Tb), dysprosium (Dy) and holmium (Ho).

[0008] According to an embodiment of the present invention, the area of ​​the RE-rich phase in the grain boundaries in the magnet occupies 6% or more of the total field area.

[0009] According to an embodiment of the present invention, the average ratio of the area of ​​the RE-rich phase at the nodular grain boundary located at the intersection of three or more main phase crystal grains to the total area of ​​all three or more surrounding adjacent main phase crystal grains is ≦15%, more preferably ≦10%, and even more preferably ≦7%.

[0010] In the present invention, the vertically oriented surface of a neodymium cerium iron boron permanent magnet is polished and detected using a field emission electron probe microanalyzer (FE-EPMA) (JEOL, 8530F), and the area occupancy is analyzed using Image-Pro Plus software.

[0011] In the present invention, the above-mentioned field of view area refers to the image display range detected by FE-EPMA or SEM, and is not limited to the magnification ratio of the test sample image, for example, 200, 500, 800, 1000 or 1500 times magnification.

[0012] In the present invention, the adjacent main phase crystal grains refer to the main phase crystal grains adjacent to the RE rich phase at the grain boundary.

[0013] According to an embodiment of the present invention, the main phase is RFe 14 It has B structure.

[0014] According to an embodiment of the present invention, the main phase crystal grains of the neodymium cerium iron boron permanent magnet have an average grain size of 5 to 10 μm.

[0015] According to an embodiment of the present invention, the neodymium cerium iron boron permanent magnet has the chemical formula (Ce a RH b R.L. 1-a-b ) x Fe 100-x-y-z TM y B z having wherein 20≦x≦40, 0.5≦y≦10, 0.9≦z≦1.5, 0.05≦a≦0.65, 0≦b≦0.25; the RH element is at least one of Dy, Tb, Ho, and Gd; the RL element is at least one selected from Pr, Nd, La, and Y and contains at least Nd; and the TM element is at least one of Co, Cu, Ga, Al, Zr, and Ti.

[0016] According to an embodiment of the present invention, the RH element is preferably Dy.

[0017] According to an embodiment of the present invention, the RL elements are preferably Pr, Nd.

[0018] According to an embodiment of the present invention, the TM elements are a mixture of Co, Cu, Ga, Al, Zr and Ti.

[0019] According to an embodiment of the present invention, 25≦x≦35, 1≦y≦5, 0.9≦z≦1.3, 0.05≦a≦0.25, and 0.01≦b≦0.1.

[0020] The present invention is a method for producing the above-mentioned NdCeFeB permanent magnet, comprising milling, pressing, sintering and aging treatment of raw materials containing Ce, RL, Fe, TM and B elements, and optionally containing or not containing RH element, to obtain the above-mentioned NdCeFeB permanent magnet, wherein the elements RL, TM and RH have the above meanings; the method further provides:

[0021] According to an embodiment of the present invention, the method includes milling, pressing and sintering raw materials including elements Ce, RL, Fe, TM, B and RH to obtain the NdCeFeB permanent magnet.

[0022] According to an embodiment of the present invention, the amount of each raw material added is (Ce a RH b R.L. 1-a-b ) x Fe100-x-y-z TM y B z Add in stoichiometric ratio.

[0023] According to an embodiment of the present invention, the permanent magnet manufacturing process may further include adding one or more lubricants selected from calcium stearate, zinc stearate, tributyl borate, isopropanol, petroleum ether, etc. Preferably, the amount of the lubricant may be 0.01-2 wt% of the total powder weight, and is illustratively 0.01 wt%, 0.05 wt%, 0.1 wt%, 0.5 wt%, 1 wt%, or 2 wt%.

[0024] According to an embodiment of the present invention, the method includes firstly manufacturing raw material containing elements Ce, RL, Fe, TM, B and RH into alloy flakes, and then the alloy flakes are subjected to hydro-crushing, dehydrogenation and grinding to manufacture alloy powder, which is then subjected to press molding, sintering and aging treatment to manufacture and obtain the NdCeFeB permanent magnet.

[0025] According to an embodiment of the present invention, the method includes: (K1) firstly preparing a main phase alloy flake not containing Ce and an auxiliary phase alloy flake containing Ce, Among them, the Ce-free main phase alloy flakes are produced by smelting and condensing the raw materials of RL, Fe, TM and B elements, and optionally the RH element, which may or may not be present, into alloy flakes; The Ce-containing auxiliary phase alloy flakes are produced by smelting and condensing a source of Ce, RL, Fe, TM and B elements, and optionally a RH element, which may or may not be present, into alloy flakes; (K2) The Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes of step (K1) are respectively subjected to hydro-crushing, dehydrogenation and jet milling to produce alloy powders, which are optionally subjected to press molding, sintering and aging treatment with or without adding a lubricant to obtain the NdCeFeB permanent magnet.

[0026] According to an embodiment of the present invention, the method includes: (K1) firstly preparing a main phase alloy flake not containing Ce and an auxiliary phase alloy flake containing Ce, Among them, the main phase alloy flakes not containing Ce are produced by smelting and condensing the raw materials of RL, RH, Fe, TM and B elements into alloy flakes, The auxiliary phase alloy flakes containing Ce are produced by smelting and condensing raw materials of Ce, RL, RH, Fe, TM and B elements into alloy flakes; (K2) The Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes of step (K1) are respectively subjected to hydro-crushing, dehydrogenation and jet milling to produce alloy powders, which are optionally subjected to press molding, sintering and aging treatment with or without adding a lubricant to obtain the NdCeFeB permanent magnet.

[0027] According to an embodiment of the present invention, in step (K2), the Ce-free main phase alloy flakes and the Ce-containing auxiliary phase alloy flakes of step (K1) are hydro-crushed, dehydrogenated and jet-milled to produce alloy powder, which is then added with a lubricant, pressed and sintered to obtain the NdCeFeB permanent magnet.

[0028] According to an embodiment of the present invention, the method includes the following steps: (S1) firstly, produce Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes, which are then subjected to hydro-crushing, dehydrogenation and jet milling to produce main phase alloy powders and auxiliary phase alloy powders; The Ce-free main phase alloy flakes and the Ce-containing auxiliary phase alloy flakes have the above-mentioned meanings, (S2) mixing the main phase alloy powder of step (S1) with the auxiliary phase alloy powder, optionally adding or not adding a lubricant, and then carrying out press molding, sintering and aging treatment to manufacture the NdCeFeB permanent magnet.

[0029] According to an embodiment of the present invention, in step (S2), the main phase alloy powder and the auxiliary phase alloy powder of step (S1) are mixed, a lubricant is added, and the mixture is pressed, sintered, and aged to produce the above-mentioned NdCeFeB permanent magnet.

[0030] According to an embodiment of the present invention, in step (S2), the mass ratio of the main phase alloy powder to the auxiliary phase alloy powder is (1-40):1, illustratively 2.7:1, 10:1. According to an embodiment of the present invention, the thickness of the alloy flakes (including the main phase alloy flakes and the auxiliary phase alloy flakes) is 0.1-0.4 mm, illustratively 0.1 mm, 0.2 mm, 0.25 mm, 0.3 mm, or 0.4 mm.

[0031] According to an embodiment of the present invention, the alloy flakes (including the main phase alloy flakes and the auxiliary phase alloy flakes) are obtained by vacuum smelting and then casting from each raw material. Illustratively, the smelting of the alloy flakes is carried out in a vacuum induction furnace.

[0032] Preferably, the smelting is carried out in an atmosphere of an inert gas, such as, for example, nitrogen gas or argon gas, preferably in an argon gas atmosphere.

[0033] Preferably, the casting temperature in the smelting process of the alloy flakes is 1300 to 1500°C, for example 1300°C, 1400°C, or 1500°C.

[0034] Preferably, the casting process of the alloy flakes is to cast the molten raw material liquid onto a rotating water-cooled copper roll, and the rotation speed of the rotating water-cooled copper roll is 15 to 45 rpm, e.g., 15 rpm, 20 rpm, 25 rpm, 30 rpm, 40 rpm, or 45 rpm.

[0035] Preferably, the average particle size of the alloy powders (including the main phase alloy powder and the auxiliary phase alloy powder) is 2 to 6 μm, e.g., 2 μm, 3 μm, 3.5 μm, 4 μm, 5 μm, 6 μm. Exemplary, the average particle size of the main phase alloy powder is 4 to 6 μm, and the average particle size of the auxiliary phase alloy powder is 3 to 5 μm.

[0036] According to an embodiment of the present invention, the method further comprises pressing the alloy powder into a billet.

[0037] According to an embodiment of the present invention, the press forming includes orientation pressing and isostatic pressing, and preferably, the billet is firstly oriented pressing and then isostatic pressing to improve the density of the billet. Furthermore, the orientation pressing is performed in a magnetic field, and the isostatic pressing is performed in an isostatic pressing machine.

[0038] Preferably, the mixed powder is subjected to orientation press molding under the protection of an inert gas atmosphere such as a nitrogen gas or argon gas atmosphere, preferably a nitrogen gas atmosphere.

[0039] Preferably, the magnetic field strength of the aligning magnetic field is 2 to 5T, illustratively 2T, 3T, 4T, or 5T.

[0040] The pressure of the isostatic molding is preferably 150 to 260 MPa, for example, 150 MPa, 180 MPa, 185 MPa, 200 MPa, 220 MPa, 240 MPa, or 260 MPa.

[0041] Preferably, the density of the billet is 4 to 6 g / cm 3 , for example 4g / cm 3 , 4.2g / cm 3 , 4.6g / cm 3 , 5g / cm 3 , 6g / cm 3 It is.

[0042] According to an embodiment of the present invention, the billet is further heat-treated before the sintering process, the heat treatment temperature is 100 to 950°C, preferably 150 to 900°C, and the heat-treatment warming time is 60 to 120 min. For example, the heat treatment temperature is 3 to 6 stages, the heat treatment temperature of each stage may be the same or different, the heat-treatment time may be the same or different, and the heat treatment stage may be performed in an inert gas or in a vacuum. For example, the heat treatment temperature is 4 stages, and is 100 to 200°C, 200 to 550°C, 550 to 700°C, and 700 to 950°C, respectively.

[0043] According to an embodiment of the present invention, the sintering is a vacuum liquid phase sintering having four or more sintering heat-retention stages, for example, four to ten sintering heat-retention stages, and the temperature of the sintering heat-retention stage is 900 to 1150°C, preferably 950 to 1100°C, e.g., 900°C, 950°C, 1000°C, 1010°C, 1015°C, 1030°C, 1040°C, 1050°C, 1070°C, 1100°C, and the heat-retention temperature of the multiple heat-retention stages may be the same or different. The heat-retention time is 40 to 140 min, preferably 50 to 100 min, e.g., 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 110 min, and the heat-retention time may be the same or different. The sintering heat-retention stage may be performed in an inert gas or in a vacuum state.

[0044] Preferably, before each of the above sintering and temperature-retaining steps, a temperature-raising step is included in which the temperature-raising rate is 0.5 to 5°C / min, more preferably 1 to 4°C / min, and the temperature-raising rates in each temperature-raising step may be the same or different.

[0045] According to an embodiment of the present invention, between two adjacent sintering and heat-retaining processes, the next temperature-raising and heat-retaining process may be performed directly after the previous sintering and heat-retaining stage is completed, or the previous sintering and heat-retaining stage may be cooled first and then the next temperature-raising and heat-retaining process may be performed. The cooling temperature is not limited as long as it is lower than the temperature of the previous sintering and heat-retaining stage, and the number of cooling stages is not particularly limited as long as it reaches the required cooling temperature. That is, any random process can be provided between two adjacent sintering and heat-retaining processes. For example, after the previous sintering and heat-retaining stage is completed, 1 to 10 cooling stages are first performed, and then the next temperature-raising and heat-retaining process is performed, and the cooling temperatures of the 1 to 10 stages may be the same or different. Exemplarily, the cooling temperature after the heat-retaining stage is 500 to 1050°C.

[0046] According to an embodiment of the present invention, the aging treatment is performed after the sintering treatment is cooled. Exemplarily, the aging treatment includes cooling to room temperature after the sintering is completed, and then performing a heating treatment.

[0047] Preferably, the aging treatment is a secondary aging treatment including a first aging treatment in which the temperature is increased to 800-950°C and the heat retention time is 160-300 min, and a second aging treatment in which the temperature is increased to between 450-600°C after cooling to below 210°C and the heat retention time is 240-360 min.

[0048] According to an embodiment of the present invention, a method for producing the above NdCeFeB permanent magnet includes the following steps.

[0049] Step 1, (Ce a RH b R.L. 1-a-b ) x Fe 100-x-y-z TM y B z The raw materials are weighed according to the components and compounding ratio, smelted in a vacuum induction furnace under the protection of an Ar gas atmosphere, the molten liquid is cast onto a rotating quench roll, and then strip-cast onto a cooling disk for cooling to produce alloy flakes.

[0050] Step 2: The alloy flakes are hydro-crushed, dehydrogenated and jet-milled to produce alloy powder.

[0051] Step 3: The alloy powder is oriented-pressed in a magnetic field to obtain a billet, which is then pressed in an isostatic press to further improve the density of the billet.

[0052] Step 4, the billet is sintered and aged in a sintering furnace with N (4≦N≦10) sintering and heat-holding stages to produce a NdCeFeB permanent magnet.

[0053] According to an embodiment of the present invention, the above method further includes a grain boundary diffusion treatment step, in which the surface of the NdCeFeB permanent magnet produced after sintering is ground, and then a heavy rare earth diffusion source is applied to produce a grain boundary diffusion NdCeFeB permanent magnet after diffusion treatment.

[0054] Preferably, the diffusion treatment includes applying a diffusion material to the magnet surface, and performing a vacuum heating diffusion treatment, a diffusion cooling and a diffusion aging treatment.

[0055] According to an embodiment of the present invention, one or more kinds of heavy rare earth RH (Dy, Tb) pure metal, alloy, compound, etc. can be attached to the surface of a neodymium cerium iron boron permanent magnet by using a spray coating method. Exemplary are at least one of pure metal of Dy and / or Tb, hydride of Dy and / or Tb, oxide of Dy and / or Tb, hydroxide of Dy and / or Tb, fluoride of Dy and / or Tb, etc., and exemplary is dysprosium fluoride.

[0056] According to an embodiment of the present invention, the diffusion process can be performed in a vacuum heat treatment furnace.

[0057] Preferably, the temperature of the vacuum thermal diffusion treatment is 800 to 980° C., and the time of the vacuum thermal diffusion treatment is 5 to 45 hours.

[0058] Preferably, the temperature of the diffusion cooling is less than 100°C.

[0059] Preferably, the temperature of the diffusion aging treatment is 420 to 650° C., for example, 550° C., and the time of the diffusion aging treatment is 3 to 10 hours.

[0060] According to embodiments of the present invention, the billet may also be machined to a target size after the sintering process and before the diffusion treatment.

[0061] The present invention further provides applications of the above NdCeFeB permanent magnets in the fields of rare earth permanent magnet motors, smart consumer electrical appliances, medical equipment and so on.

[0062] The beneficial effects of the present invention are as follows:

[0063] The present invention prepares the base compound, manufacturing method and sintering system of NdFeB to reduce the migration distance from the solid-liquid interface to the solid phase on the surface of the main phase grains of NdFeB, delay the melting of the main phase grains, inhibit the growth of the main phase grains, and at the same time, strengthen the capillary action of the grain boundaries, distribute the molten RE-rich phase along the grain boundaries, reduce the ratio of the area of ​​the RE-rich phase in the nodular grain boundaries located at the intersections of three or more main phase grains to the total area of ​​all three or more surrounding adjacent grains, reduce the area ratio of the RE-rich phase in the magnet occupying the entire field area, and distribute it uniformly and finely. At the same time, the RE-rich phase in the continuous and smooth thin grain boundaries is formed to divide and surround the main phase grains, repair the grain boundary defects, thereby inhibiting the nucleation of the reverse magnetization domain, inhibiting the movement of the reverse magnetization domain wall, and effectively blocking the magnetic exchange coupling action between the main phase grains, and further makes the permanent magnet have a relatively high magnetic performance.

[0064] The addition of Ce changes the composition and structural form of the grain boundary phase in the magnet, lowers the melting point of the RE-rich phase, lowers the sintering and aging temperature of the magnet, and at the same time tends to distribute the RE-rich phase in the grain boundary in a nodular shape. With the increase of Ce content, the tendency of the grain boundary phase to distribute in a nodular shape becomes more pronounced, which increases the grain boundary defects and causes the main phase crystal grains to contact each other, thereby reducing the magnetic performance. Therefore, the present invention further extends the sintering period and increases the heat retention time to promote the distribution of the molten RE-rich phase along the main phase crystal grains, improve the ratio of the RE-rich phase in the two grain boundaries, distribute it uniformly and finely in the magnet, reduce defects, suppress the nucleation of reverse magnetization domains, and achieve the purpose of optimizing the magnet microstructure and magnetic performance.

[0065] In addition, the magnet produced by the present invention has excellent diffusion effect when used as a grain boundary diffusion magnet substrate, because the RE-rich phase in the magnet is continuously distributed along the grain boundary, providing many channels for diffusion, which is helpful to improve the diffusion depth from the diffusion source to the inside of the magnet, which is helpful to improve the distribution uniformity of the diffusion source inside the magnet, which is helpful to improve the consistency of the internal structure components of the diffusion magnet, thereby further improving the magnetic performance of the diffusion magnet. [Brief description of the drawings]

[0066] [Figure 1] 1 is a scanning electron microscope image of the grain boundary phase and main phase in the magnet of Comparative Example 2. [Diagram 2] 1 is a scanning electron microscope image of the grain boundary phase and main phase in the magnet of Example 1. [Diagram 3] FIG. 2 is a distribution diagram of the RE-rich phase at the nodular grain boundary at the intersection of three or more main phase grains and all the surrounding three or more adjacent main phase grains according to the present invention.

[0067] [Mode for carrying out the invention] The technical solution of the present invention will be described in more detail below with reference to specific examples. It should be understood that the following examples are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of the claims of the present invention. Any technology realized based on the above content of the present invention is included in the scope of the claims of the present invention.

[0068] Unless otherwise specified, all materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0069] In the following examples of the present invention, PrNd is added in the form of an alloy, the remaining metals are all added in elemental form, and B is provided by B-Fe sand.

[0070] Example 1 (1) In accordance with the design mixing ratio of PrNd: 29 wt.%, Ce: 3.7 wt.%, Dy: 0.4 wt.%, Co: 1.2 wt.%, Cu: 0.3 wt.%, Ga: 0.1 wt.%, Al: 0.53 wt.%, Zr: 0.12 wt.%, Ti: 0.12 wt.%, B: 0.99 wt.%, and Fe balance, based on 100 mass% of the components, the raw materials were weighed and smelted using a vacuum induction smelting furnace under the protection of an Ar gas atmosphere, and the molten liquid was cast onto a quenching roll rotating at a speed of 32 rpm. The liquid casting temperature was 1400°C, and alloy flakes with an average thickness of 0.25 mm were produced.

[0071] (2) The alloy flakes were subjected to hydro-crushing, dehydrogenation, and jet milling to produce alloy powder with an average particle size of 3.7 μm. The alloy powder was then protected under a N2 atmosphere and mixed with the lubricant zinc stearate, which accounted for 0.05 wt% of the alloy powder weight, by stirring to homogeneously mix the powder.

[0072] (3) The mixed powder of step (2) is filled into the press mold cavity under the protection of a N2 atmosphere, and then pressed by orientation molding with an orientation magnetic field strength of 3T. Then, in an isostatic press, a pressure of 185 MPa is applied and the pressure is maintained for 8 s to perform isostatic pressing, resulting in a density of 4.2 g / cm. 3 The billet was obtained.

[0073] (4) The billet was placed in a sintering furnace and heated in a vacuum atmosphere. It was then kept at 150°C and 260°C for 100 min each to remove the lubricant, and kept at 600°C and 900°C for 90 min each to remove the gas. Then, a four-stage sintering and heat-holding process was carried out. After each sintering and heat-holding stage, the temperature was first lowered to 1000°C, and then further increased, and the next heating process was carried out. The specific sintering process is shown in Table 1. After the fourth sintering and heat-holding stage, the billet was directly cooled to room temperature to obtain a sintered compact.

[0074] (5) Aging treatment: The sintered body is taken, heated to 900°C and kept at that temperature for 180 minutes, then cooled to 200°C, and then further heated to 530°C and kept at that temperature for 240 minutes. After the temperature keeping is completed, the magnet is cooled to room temperature to obtain a magnet after aging treatment. The neodymium cerium iron boron permanent magnet has the chemical formula (Ce 0.11 RH 0.01 R.L. 0.88 ) 33.1 Fe 63.56 TM 2.35 B 0.99 had.

[0075] The RH element was Dy, the RL elements were Pr, Nd, and the TM elements were Co, Cu, Ga, Al, Zr, and Ti.

[0076] Fig. 2 is a scanning electron microscope image of the grain boundary phase and main phase in the magnet of Example 1. As can be seen from Fig. 2, the distribution of the RE-rich phase was uniform and fine.

[0077] Example 2 Example 2 uses the same compounding, smelting, milling, press molding, and aging processes as Example 1, with the only difference being that it uses a five-stage sintering and heat-retaining process. The specific sintering process is shown in Table 1.

[0078] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is only the sintering process, in which the temperature is raised according to the conventional sintering process and a single warming sintering treatment is performed. The specific sintering process is shown in Table 1.

[0079] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses a three-stage sintering and heat-retention process, and after each sintering and heat-retention stage, the temperature is first lowered to 1000°C and then further increased to perform the next heating process. The specific sintering process is shown in Table 1.

[0080] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is the composition ratio of the components: PrNd: 32.2 wt.%, Ce: 0.5 wt.%, Dy: 0.4 wt.%, Co: 1.2 wt.%, Cu: 0.3 wt.%, Ga: 0.1 wt.%, Al: 0.53%, Zr: 0.12 wt.%, Ti: 0.12 wt.%, B: 0.99 wt.%, Fe balance. The manufacturing method is completely the same as Example 1, and the neodymium cerium iron boron permanent magnet is represented by the chemical formula (Ce 0.02 RH 0.01 R.L. 0.97 ) 33.1 Fe 63.56 TM 2.35 B 0.99 had.

[0081] The RH element was Dy, the RL elements were Pr, Nd, and the TM elements were Co, Cu, Ga, Al, Zr, and Ti.

[0082] FIG. 1 is a scanning electron microscope image of the grain boundary phase and main phase in the magnet of Comparative Example 2. As can be seen from FIG. 1, the distribution of the RE-rich phase was coarse and non-uniform.

[0083] Comparative Example 4 The only difference between Comparative Example 4 and Comparative Example 3 is that a three-stage sintering and heat-retaining process is used. The specific sintering process is shown in Table 1.

[0084] [Table 1]

[0085] [Table 2]

[0086] Example 3 In Example 3, the sintered and aged magnet from Example 1 was selected and processed into a sheet product with a length of 20 mm, a width of 20 mm and a thickness of 5 mm, and a thin film of dysprosium fluoride with a thickness of 1 mm was added to the magnet surface by a dip coating process, and then the magnet was diffused at 900°C for 15 hours, cooled to a diffusion temperature below 100°C, and then further heated to 550°C for aging for 5 hours to produce a grain boundary diffusion NdFeB permanent magnet. The final magnet was subjected to a magnetic performance test.

[0087] Comparative Example 5 In Example 5, the sintered and aged magnet from Comparative Example 2 was selected and processed into a sheet product with a length of 20 mm, a width of 20 mm and a thickness of 5 mm, and a thin film of dysprosium fluoride with a thickness of 1 mm was added to the magnet surface by a dip coating process, and then the magnet was diffused at 900°C for 15 hours, cooled to a diffusion temperature below 100°C, and then further heated to 550°C for aging for 5 hours to produce a grain boundary diffusion NdFeB permanent magnet. The final magnet was subjected to a magnetic performance test.

[0088] Example 4 (1) Based on the design composition ratio of 100 mass% of the components, PrNd: 32.6 wt.%, Dy: 0.4 wt.%, Co: 1.3 wt.%, Cu: 0.38 wt.%, Ga: 0.1 wt.%, Al: 0.6 wt.%, Ti: 0.14 wt.%, Zr: 0.1 wt.%, B: 0.99 wt.%, and Fe balance, the main phase alloy raw materials were weighed out and smelted using a vacuum induction smelting furnace under the protection of an Ar gas atmosphere, and the molten liquid was cast onto a water-cooled copper roll rotating at a speed of 32 rpm. The liquid casting temperature was 1400°C, and main phase alloy flakes with an average thickness of 0.27 mm were produced.

[0089] (2) In accordance with the design mixing ratio of PrNd: 19.3 wt.%, Ce: 13.7 wt.%, Dy: 0.4 wt.%, Co: 1.3 wt.%, Cu: 0.1 wt.%, Ga: 0.1 wt.%, Al: 0.35 wt.%, Ti: 0.1 wt.%, Zr: 0.1 wt.%, B: 0.99 wt.%, and Fe balance, based on 100 mass% of the components, the auxiliary phase alloy raw materials were weighed out and smelted using a vacuum induction smelting furnace under the protection of an Ar gas atmosphere, and the molten liquid was cast onto a water-cooled copper roll with a rotation speed of 36 rpm. The liquid casting temperature was 1400°C, and auxiliary phase alloy flakes with an average thickness of 0.25 mm were produced.

[0090] (3) The main phase alloy flakes and auxiliary phase alloy flakes were subjected to hydro-crushing, dehydrogenation, and jet milling to produce alloy powders with average particle sizes of 5 μm and 3.5 μm, respectively. These were then mixed in a mass ratio of 2.7:1 under the protection of a N2 atmosphere, and the alloy powders were added with the lubricant tributyl borate, which accounted for 0.05 wt%, and stirred to mix uniformly.

[0091] (4) The mixed powder is filled into a press mold cavity under the protection of a N2 atmosphere, and then oriented molding pressed with an orientation magnetic field strength of 3T. Then, in an isostatic press, it is isostatically pressed at a pressure of 185 MPa for 8 s, and the density is 4.2 g / cm. 3 The billet was obtained.

[0092] (5) The billet was placed in a sintering furnace and heated in a vacuum atmosphere. It was then kept at 150°C and 260°C for 100 min each to remove the lubricant, and kept at 600°C and 900°C for 90 min each to remove the gas. Then, four stages of sintering and keeping were carried out. After each sintering and keeping stage was completed, the temperature was first lowered to 990°C, and then further increased to carry out the next heating process. The specific sintering process is shown in Table 2. After the fourth sintering and keeping stage was completed, the billet was directly cooled to room temperature to obtain a sintered compact.

[0093] (6) Aging treatment: The sintered body is taken, heated to 900°C and kept at that temperature for 180 minutes, then cooled to 200°C, and then further heated to 530°C and kept at that temperature for 240 minutes. After the temperature keeping is completed, the magnet is cooled to room temperature to obtain a magnet after aging treatment. The neodymium cerium iron boron permanent magnet has the chemical formula (Ce 0.11RH 0.01 R.L. 0.88 ) 33.1 Fe 63.56 TM 2.35 B 0.99 had.

[0094] The RH element was Dy, the RL elements were Pr, Nd, and the TM elements were Co, Cu, Ga, Al, Zr, and Ti.

[0095] Comparative Example 6 The difference between Comparative Example 6 and Example 4 is that Comparative Example 6 uses a three-stage sintering and heat-retaining process, and the specific sintering process is shown in Table 2.

[0096] Example 5 The only difference between Example 5 and Example 4 is the milling step (3). In Example 5, the main phase alloy flakes and the auxiliary phase alloy flakes were mixed in a mass ratio of 2.7:1, then hydrogen crushed, dehydrogenated, and jet milled to produce alloy powder with an average particle size of 3.7 μm. The alloy powder was protected under a N2 atmosphere and added with 0.05 wt% of lubricant tributyl borate, and stirred to mix uniformly.

[0097] Comparative Example 7 The difference between Comparative Example 7 and Example 5 is that Comparative Example 7 uses a three-stage sintering and heat-retaining process, and the specific sintering process is shown in Table 2.

[0098] [Table 3]

[0099] [Table 4]

[0100] All of the magnets after aging treatment in each of Examples 1 to 5 and Comparative Examples 1 to 7 were processed into standard φ10-10 sample columns, and the magnet performance was measured using a BH device. Specific magnetic performance test results.

[0101] The magnetic performance of the magnets manufactured in the above Examples 1 to 5 and Comparative Examples 1 to 7 was measured using a NIM-62000 permanent magnet material precision measurement system, and detected using a field emission electron probe microanalyzer (FE-EPMA) (JEOL, 8530F). The area occupancy was analyzed using Image-Pro Plus software, and the results are shown in Table 3 below.

[0102] Among them, the ratio of the area of ​​the RE-rich phase to the total field of view was expressed as the area ratio S1.

[0103] The average ratio of the sum of the areas of the RE-rich phase in the nodular grain boundaries located at the intersections of three or more main phase grains to the sum of the total areas of all three or more surrounding adjacent main phase grains was S2.

[0104] The average grain size was the average grain size of the main phase crystal grains.

[0105] [Table 5] As can be seen from the comparison between Example 1 and Comparative Example 1, the use of the four-stage sintering and temperature-retaining process effectively reduced the area ratio of the RE-rich phase in the nodular grain boundary phase, further refined the RE-rich phase in the grain boundary phase, and significantly improved the magnetic performance of the magnet.

[0106] As can be seen from the comparison between Example 1, Example 2, and Comparative Example 2, the magnet performance can be further improved by using a five-stage sintering and heat-retaining process, and the improvement effect is limited. However, the performance improvement effect of the four-stage sintering and heat-retaining process (see Example 1) is clearly superior to that of the three-stage sintering and heat-retaining process (see Comparative Example 2).

[0107] The improvement in magnetic performance, S1, S2 between Example 1 and Comparative Example 2 is clearly greater than the improvement in magnetic performance, S1, S2 between Comparative Example 3 and Comparative Example 4, indicating that the performance improvement effect of the four-stage sintering and heat retention process for magnets with a high Ce content is clearly superior to magnets with a low Ce content.

[0108] As can be seen from a comparison between Example 3 and Comparative Example 5, the grain boundary phase distribution can be optimized by using a four-stage sintering and temperature-retention process, thereby significantly improving the diffusion effect of the magnet.

[0109] As can be seen from the comparison between Example 4 and Comparative Example 6, and Example 5 and Comparative Example 7, the magnetic performance of the dual-alloy magnets produced using the four-stage sintering and holding process was also superior to that produced using the three-stage sintering and holding process.

[0110] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention are intended to be included in the scope of the claims of the present invention.

Claims

1. A neodymium cerium iron boron permanent magnet, The area of ​​the RE-rich phase in the grain boundaries in the magnet occupies 4% or more of the total field area. The RE-rich phase is uniformly and finely distributed at the grain boundaries within the magnet. The average ratio of the area of ​​the RE-rich phase at the nodular grain boundaries located at the intersections of three or more main phase crystal grains to the total area of ​​all three or more surrounding adjacent main phase crystal grains is ≦30%. Neodymium cerium iron boron permanent magnet.

2. The RE includes neodymium (Nd) and may further include at least one selected from the rare earth elements cerium (Ce), lanthanum (La), praseodymium (Pr), yttrium (Y), gadolinium (Gd), terbium (Tb), dysprosium (Dy) and holmium (Ho); Preferably, the area of ​​the RE-rich phase in the grain boundaries in the magnet occupies 6% or more of the total field area, Preferably, the average ratio of the area of ​​the RE-rich phase at the nodular grain boundary located at the intersection of three or more main phase crystal grains to the total area of ​​all three or more adjacent main phase crystal grains around the nodular grain boundary is ≦15%, more preferably ≦10%, and even more preferably ≦7%; Preferably, the main phase is R 2 Fe 14 B structure, Preferably, the average grain size of the main phase crystal grains of the neodymium cerium iron boron permanent magnet is 5 to 10 μm.

2. The neodymium cerium iron boron permanent magnet according to claim 1.

3. The neodymium cerium iron boron permanent magnet has the chemical formula (Ce a R.H. b R.L. 1-a-b ) x Fe 100-x-y-z T.M. y B z having wherein 20≦x≦40, 0.5≦y≦10, 0.9≦z≦1.5, 0.05≦a≦0.65, and 0≦b≦0.25; the RH element is at least one of Dy, Tb, Ho, and Gd; the RL element is at least one selected from Pr, Nd, La, and Y, and contains at least Nd; and the TM element is at least one of Co, Cu, Ga, Al, Zr, and Ti; Preferably, 25≦x≦35, 1≦y≦5, 0.9≦z≦1.3, 0.05≦a≦0.25, and 0.01≦b≦0.

1.

3. The neodymium cerium iron boron permanent magnet according to claim 1 or 2.

4. A method for producing the neodymium cerium iron boron permanent magnet according to any one of claims 1 to 3, A raw material containing Ce, RL, Fe, TM, B, and optionally present or absent RH element is milled, pressed, sintered, and aged to obtain the neodymium cerium iron boron permanent magnet; Preferably, the method includes milling, pressing and sintering a raw material containing Ce, RL, Fe, TM, B and RH elements to obtain the NdCeFeB permanent magnet, Preferably, in the method, one or more lubricants selected from calcium stearate, zinc stearate, tributyl borate, isopropanol, and petroleum ether are further added, and preferably, the dosage of the lubricant can be 0.01-2 wt% of the total powder weight; A manufacturing method comprising the steps of:

5. The method includes: (K1) first producing a main phase alloy flake not containing Ce and an auxiliary phase alloy flake containing Ce; Among them, the Ce-free main phase alloy flakes are produced by smelting and condensing the raw materials of RL, Fe, TM and B elements, and optionally present or absent RH elements, into alloy flakes; The Ce-containing auxiliary phase alloy flakes are produced by smelting and condensing a source of Ce, RL, Fe, TM and B elements, and optionally a RH element, which may or may not be present, into alloy flakes; (K2) The Ce-free main phase alloy flakes and the Ce-containing auxiliary phase alloy flakes of step (K1) are respectively subjected to hydro-crushing, dehydrogenation and jet milling to produce alloy powder, which is optionally press-molded, sintered and aged to obtain the NdCeFeB permanent magnet; Preferably, the method includes the steps of: (S1) first producing Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes, which are then subjected to hydro-crushing, dehydrogenation and jet milling to produce main phase alloy powder and auxiliary phase alloy powder, respectively; The Ce-free main phase alloy flakes and the Ce-containing auxiliary phase alloy flakes have the above-mentioned meanings, (S2) mixing the main phase alloy powder and the auxiliary phase alloy powder of step (S1), optionally adding or not adding a lubricant, and then carrying out press molding, sintering and aging treatment to obtain the NdCeFeB permanent magnet; Preferably, in step (S2), the main phase alloy powder and the auxiliary phase alloy powder of step (S1) are mixed, a lubricant is added, and the mixture is press-molded, sintered, and aged to obtain the NdCeFeB permanent magnet; Preferably, in step (S2), the mass ratio of the main phase alloy powder to the auxiliary phase alloy powder is (1-40):1; The method according to claim 4 .

6. The method further comprises pressing the alloy powder into a billet; Preferably, the press molding includes oriented press molding and isostatic pressing, Preferably, the magnetic field strength of the aligning magnetic field is 2 to 5 T; Preferably, the pressure of the isostatic pressing is 150 to 260 MPa; Preferably, the density of the billet is between 4 and 6 g / cm 3 That is, The method according to claim 4 or 5.

7. The sintering is a vacuum liquid phase sintering having four or more sintering heat-retention stages, for example, 4 to 10 sintering heat-retention stages, the temperature of the sintering heat-retention stage is 900 to 1150°C, the heat-retention temperatures of the multiple heat-retention stages are the same or different, and the heat-retention time is 40 to 140 min; Preferably, the sintering step includes a heating step having a heating rate of 0.5 to 5°C / min, more preferably 1 to 4°C / min, prior to any of the sintering and maintaining steps; Preferably, between each two adjacent sintering and heat-retaining processes, the next temperature-raising and heat-retaining process is directly carried out after the previous sintering and heat-retaining stage is completed, or the previous sintering and heat-retaining stage is first cooled and then the next temperature-raising and heat-retaining process is carried out after the previous sintering and heat-retaining stage is completed; preferably, the previous sintering and heat-retaining stage is first cooled by 1 to 10 stages and then the next temperature-raising and heat-retaining process is carried out; preferably, the cooling temperature after the heat-retaining stage is completed is 500 to 1050°C; The method according to any one of claims 4 to 6.

8. The aging treatment is carried out after the sintering treatment and cooling; Preferably, the aging treatment is a secondary aging treatment including: a first aging treatment in which the temperature is increased to 800 to 950°C and the heat-retention time is 160 to 300 min; and a second aging treatment in which the temperature is increased to between 450 to 600°C and the heat-retention time is 240 to 360 min after cooling to 210°C or less. The method according to any one of claims 4 to 7.

9. The method further includes a grain boundary diffusion step, which comprises grinding the surface of the NdCeFeB permanent magnet produced after sintering, and then coating the heavy rare earth diffusion source to produce a grain boundary diffusion NdCeFeB permanent magnet after diffusion treatment. The method according to any one of claims 4 to 8.

10. Application of the NdCeFeB permanent magnet according to any one of claims 1 to 3 in rare earth permanent magnet motor, smart consumer electrical appliances and medical equipment fields.

Citation Information

Patent Citations

  • R-T-B based sintered magnet

    CN106057391A

  • Sintering method of neodymium-iron-boron magnet

    CN106252012A

  • R-t-b based permanent magnet

    CN109935432A

  • Permanent magnet and rotary machine

    CN110537232A

  • Rare-earth permanent magnet and method of manufacturing the same

    CN113496798A